Magmatism and Extension in the Foreland and Near-Trench Region of Collisional and Convergent Tectonic Systems - Schoonmaker, Adam; Kidd, William; Ashcroft, Tristan (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
Foreland magmatism occurs in the lower plate during arc–continent or continent–continent collision, although it is uncommon. Ancient examples are recognized by a stratigraphic section into which mafic lavas and/or shallow sills are emplaced at a level at the top of a passive margin cover sequence, or within the overlying deeper water deposits that include mudrocks and flysch-type turbidites. Extensional structures associated with the emplacement of the volcanic rocks may develop slightly prior to or contemporaneous with the arrival of the approaching thrust front. We have selected twelve examples of magmatism in collisional forelands, modern and ancient, and have compared the tectonic associations of the magmatism with the magmatic geochemistry. Foreland magmatic settings fall into two strikingly distinct geochemical groups: a more enriched alkaline group (Rhinetype) and a more heterogeneous tholeiitic group (Maine-type) that may show traces of prior subduction processes. In the examples where the contemporaneous extensional structures are known, faults and basins develop parallel to the thrust front for the tholeiitic group and have oblique orientations, in several cases at a high angle to the thrust front, for the alkaline group. The geochemical results are quite sufficiently distinct to permit discrimination of these two foreland magmatic rock suites from each other in ancient examples where the foreland setting is clear from geological evidence. However, magmatic products of the same range of compositions can be generated in other tectonic environments (rifts, back-arc basins), so the geochemical characteristics alone are insufficient to identify a foreland basin setting. The alkaline Rhine-type group formed primarily in response to localized upwelling convective activity from the sub-asthenospheric mantle beneath the lower plate during collision while the tholeiitic Maine-type group formed primarily in response to melting of subcontinental asthenospheric mantle during extension of the lower plate by slab pull, and resulting lithospheric detachment. It is possible that there has been a long-term secular decrease in the occurrence of the Mainetype foreland magmatism since the early Proterozoic.